2011
DOI: 10.1128/mcb.01211-10
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Inhibitor of the Canonical Wnt Pathway

Abstract: Wnt signaling is known to regulate multiple processes including angiogenesis, inflammation, and fibrosis. Here, we identified a novel inhibitor of the Wnt pathway, pigment epithelium-derived factor (PEDF), a multifunctional serine proteinase inhibitor. Both overexpression of PEDF in transgenic mice and administration of PEDF protein attenuated Wnt signaling induced by retinal ischemia. Furthermore, PEDF knockdown by small interfering RNA (siRNA) and PEDF knockout in PEDF ؊/؊ mice induced activation of Wnt sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
129
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(135 citation statements)
references
References 80 publications
5
129
0
1
Order By: Relevance
“…Although PEDF's effect on TSP-1 is one notable effect, additional mechanisms underlying PEDF's ability to maintain the integrity of the extracellular matrix remain to be investigated. A recent study 47 identified PEDF as an endogenous antagonist of LRP6, a coreceptor for the canonical Wnt-␤-catenin signaling pathway. In the liver, constitutive activation of Wnt-␤-catenin signaling yielded defective hepatocyte differentiation but fully developed bile ducts that led to remodeling of the ductal plate.…”
Section: Discussionmentioning
confidence: 99%
“…Although PEDF's effect on TSP-1 is one notable effect, additional mechanisms underlying PEDF's ability to maintain the integrity of the extracellular matrix remain to be investigated. A recent study 47 identified PEDF as an endogenous antagonist of LRP6, a coreceptor for the canonical Wnt-␤-catenin signaling pathway. In the liver, constitutive activation of Wnt-␤-catenin signaling yielded defective hepatocyte differentiation but fully developed bile ducts that led to remodeling of the ductal plate.…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches seeking to reduce AGE interactions, either by inhibiting AGE formation, blocking AGE action, or breaking preexisting AGE cross-links, have been explored. Recently Park et al [30,79,82] have identified a novel inhibitor of the Wnt pathway that is a pigment epithelium-derived factor (PEDF), a multifunctional serine proteinase inhibitor. They have reported that overexpression of PEDF in transgenic mice as well as administration of PEDF protein attenuated Wnt signaling induced by retinal ischemia.…”
Section: Age Inhibitors and Prevention Of Retinopathymentioning
confidence: 99%
“…This drug is a potent inhibitor of AGE-mediated cross-linking and has been shown to prevent diabetic vascular complications, including diabetic retinopathy, in experimental animals [82]. Blockade of the AGE/RAGE interaction by soluble RAGE has been shown to suppress nephropathy in diabetic animals [83].…”
Section: Age Inhibitors and Prevention Of Retinopathymentioning
confidence: 99%
“…We have identified the novel gene PNPLA2 in the retina that encodes a lipase-linked cell membrane protein with high affinity for PEDF and termed it PEDF-R (26). Later, other PEDF-binding proteins were reported in endothelial and tumor cells (37/67-kDa non-integrin laminin receptor (27) and cell surface F 1 F 0 -ATP synthase (28,29)) and * This work was supported, in whole or in part, by the National Institutes of on ARPE-19 cells (LRP6, a Wnt co-receptor (30)). However, it is not yet known if PEDF-R is a functional receptor for PEDF activity on the retina.…”
mentioning
confidence: 99%